Progressed Multivessel Spontaneous Coronary Artery Dissection That Naturally Healed in a Male Patient with Non-ST Segment Elevation Myocardial Infarction - Tatsuo Haraki; Ryota Uemura; Shin-ichiro Masuda; Takeshi Lee (Case Reports in Cardiology)
Spontaneous coronary artery dissection (SCAD) is a rare condition that may have a serious outcome because of acute coronary syndrome. The condition especially affects young women. We evaluated a middle-aged male patient with a non-ST segment elevation myocardial infarction caused by multivessel SCAD. The SCAD had occurred in the distal right coronary artery (RCA), the mid left anterior descending artery (LAD), and the distal LAD at the same time. His culprit lesion was in the distal RCA, but the SCAD had progressed more proximally within the RCA 12 days later with no clinical symptoms. We treated the mid LAD with implantation of a drug-eluting stent on admission and the SCAD had not progressed 12 days later. Moreover, the SCAD in the distal RCA and distal LAD healed spontaneously 12 days later. He had no recurrent attack, and all SCAD lesions of the RCA and LAD had completely healed 6 months later. Given that SCAD appears in various forms over the clinical course, a strategy of intervention needs careful consideration.